2016
DOI: 10.1002/cbin.10576
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of connexin 43 during cell division

Abstract: Gap junction channels, once clustered into gap junction plaques, allow communication of essential metabolites between cells. Gap junction plaques have been reported to be lost from the cell surface during cell division. The mechanism involved in this loss of gap junction plaques during mitosis is unclear, but we hypothesize that an endoexocytotic mechanism that results in cytoplasmic double-membraned annular gap junction vesicles is involved. In this study, gap junction plaque changes in dividing cells were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…Alternatively, Cx43 might undergo recycling from the multivesicular endosomes to the plasma membrane. In accordance with this model, Cx43 has been shown to be transported to early endosomes during the early phases of mitosis and is thought to undergo recycling to the plasma membrane in the late phases (Boassa et al, 2010;Fykerud et al, 2016;Vanderpuye et al, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…Alternatively, Cx43 might undergo recycling from the multivesicular endosomes to the plasma membrane. In accordance with this model, Cx43 has been shown to be transported to early endosomes during the early phases of mitosis and is thought to undergo recycling to the plasma membrane in the late phases (Boassa et al, 2010;Fykerud et al, 2016;Vanderpuye et al, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…We speculate that the interaction between Cx43 junctional complex and tight junction ZO proteins, or with molecules like Par3 that are involved in the PI3K-AKT pathway controlling MSO (Tenvooren et al, 2019), might underlie Cx43mediated MSO. It is unlikely that Cx43 exerts an impact on MSO via its known interaction with tubulin (Sorgen et al, 2018;Vanderpuye et al, 2016), since we rarely observed Cx43 localized near the mitotic spindle (Fig. S6C).…”
Section: Cx43 Controls the Direction Of Cell Divisionmentioning
confidence: 92%
“…Moreover, connexosomes have been suggested to be able to undergo a transformation into a connexin-enriched multivesicular endosome, which is associated with their fusion with early endosomes [79][80][81][82]. Some studies also indicate that following endocytosis, connexins can under certain conditions undergo recycling from endocytic compartments back to the plasma membrane [32, 75,81,[83][84][85]. It has also been suggested that Cx43 can be transported directly from early secretory compartments to lysosomes without prior transport to the plasma membrane [30].…”
Section: Endocytosis and Degradation Of Gap Junctionsmentioning
confidence: 99%